1991
DOI: 10.1029/91jb02103
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional velocity structure and hypocenters of earthquakes beneath the Hazara Arc, Pakistan: Geometry of the underthrusting Indian Plate

Abstract: The three-dimensional P and S wave velocity stmctures and hypocenters of 420 events beneath the westem Hazara Arc are obtained simultaneously by inverting travel time data observed at fifteen Tarbela seismic stations. In general, the P and S wave velocity distribution of the top layer (0-6 km depth) correlates well with surface geology. Within this layer we find a low-velocity region beneath the Hazara Thrust Zone (HTZ) corresponding to the underthmsted Murree Formation, and there are high-velocity regions sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…The 28 December 1974, Pattan earthquake (m b 6), another destructive earthquake that occurred before the 2005 Muzaffarabad earthquake was also due to the IKSZ. This zone was first identified by Armbruster et al (1978) using micro-earthquake survey data (1973)(1974) and is further confirmed by Seeber & Armbruster (1979) and Ni et al (1991). The IKSZ is believed to be divided into two zones, i.e.…”
Section: Seismotectonicsmentioning
confidence: 80%
“…The 28 December 1974, Pattan earthquake (m b 6), another destructive earthquake that occurred before the 2005 Muzaffarabad earthquake was also due to the IKSZ. This zone was first identified by Armbruster et al (1978) using micro-earthquake survey data (1973)(1974) and is further confirmed by Seeber & Armbruster (1979) and Ni et al (1991). The IKSZ is believed to be divided into two zones, i.e.…”
Section: Seismotectonicsmentioning
confidence: 80%
“…The top of this layer is at approximately 13 km depth and its maximum thickness is about 5 km. This mid-crustal layer, to the northeast of Hazara Syntaxis, may represent the leading edge of a slab detached from the basement of the Indian plate as suggested by NI et al (1991). The base of the low velocity layer has a velocity of 6.2 km s )1 similar to that towards the southeast.…”
Section: Discussionmentioning
confidence: 96%
“…The base of the low velocity layer has a velocity of 6.2 km s )1 similar to that towards the southeast. The velocity model of NI et al (1991) shows a continuous increase of velocity from 5.9 km s )1 (5-8 km depth) to 6.6 km s )1 (maximum 30 km depth) to the southwest of Hazara Syntaxis. They do not agree with the presence of a mid-crustal low velocity zone (LVZ), between Lawrencepur and Hazara Syntaxis shown by GUERRA et al (1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations